Evaluating investment in quality improvement capacity building: a systematic review. Issue 2 (20th February 2017) - Mery, Gustavo; Dobrow, Mark J; Baker, G Ross; Im, Jennifer; Brown, Adalsteinn
Abstract : Purpose: Leading health systems have invested in substantial quality improvement (QI) capacity building, but little is known about the aggregate effect of these investments at the health system level. We conducted a systematic review to identify key steps and elements that should be considered for system-level evaluations of investment in QI capacity building. Methods: We searched for evaluations of QI capacity building and evaluations of QI training programmes. We included the most relevant indexed databases in the field and a strategic search of the grey literature. The latter included direct electronic scanning of 85 relevant government and institutional websites internationally. Data were extracted regarding evaluation design and common assessment themes and components. Results: 48 articles met the inclusion criteria. 46 articles described initiative-level non-economic evaluations of QI capacity building/training, while 2 studies included economic evaluations of QI capacity building/training, also at the initiative level. No system-level QI capacity building/training evaluations were found. We identified 17 evaluation components that fit within 5 overarching dimensions (characteristics of QI training; characteristics of QI activity; individual capacity; organisational capacity and impact) that should be considered in evaluations of QI capacity building. 8 key steps in return-on-investment (ROI) assessments in QI capacity building were identified: (1) planning—stakeholder perspective; (2) planning—temporal perspective; (3) identifying costs; (4) identifying benefits; (5) identifying intangible benefits that will not be included in the ROI estimation; (6) discerning attribution; (7) ROI calculations; (8) sensitivity analysis. Conclusions: The literature on QI capacity building evaluation is limited in the number and scope of studies. Our findings, summarised in a Framework to Guide Evaluations of QI Capacity Building, can be used to start closing this knowledge gap.